Needs Analysis of Digital Evaluation Tool: Using Quizwhizzer for Arabic Tarkib Assessment Among Eighth Grade Students MTsN 1 Padang - Mutia Lutfi; Asrina Asrina; Hanomi Hanomi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to analyze the need for QuizWhizzer as an evaluation tool in the Arabic language tarkib test for eighth-grade students at Madrasah Tsanawiyah Negeri 1 Padang City. This study used a mixed methods approach, combining qualitative and quantitative approaches to obtain a more comprehensive picture of the need for such an evaluation tool. Data collection techniques included observation, interviews, and expert validation of questionnaires. The study subjects consisted of 29 eighth-grade VIII.1 students and one Arabic language teacher. Data were collected over a two-week period through validated questionnaires and semi-structured interviews. The results showed that the learning evaluations currently conducted by teachers still use conventional methods, using paper and pen, which are time-consuming. Meanwhile, students expressed a desire to be able to see the evaluation results directly. Based on the questionnaire data, the need for analysis from teachers reached 85%, while from students it was 80%. These findings indicate that both teachers and students have a high need for the implementation of digital-based evaluation tools, particularly the use of QuizWhizzer in the Arabic language tarkib test.